A case of severe side effect due to muscle oil injections in combination with chemotherapy in a former bodybuilder. Issue 7 (23rd July 2021) - Gitz‐Johansen, Gro; Als, Anne Birgitte; Pallesen, Kristine Appel Uldall
Abstract: This case report presents an acute painful skin reaction several years after injection of site‐enhancing oils (SEO) induced by chemotherapy. This case exemplifies the long‐term dangerous side effects of the use of SEO, however treatable with prednisolone. Abstract : This case report presents an acute painful skin reaction several years after injection of site‐enhancing oils (SEO) induced by chemotherapy. This case exemplifies the long‐term dangerous side effects of the use of SEO, however treatable with prednisolone.